On the benefits of sleep - Nature Research (16552612) (2015)
The American author Edgar Allen Poe famously loathed it, referring to it as “little slices of death”, but we now know that sleep plays an important role in physical and mental health. It is well known that sleep deprivation can significantly affect cognitive functions such as attention and memory. More recently, sleep disturbances have been linked to a wide variety of conditions, from psychiatric disorders such as depression to neurodegenerative diseases such as Alzheimer’s and Parkinson’s. Disruptions in the circadian rhythm, or the “biological clock” of the body, are also associated with increased risk of cancer, heart disease, and metabolic disorders. The incidence of these conditions is increasing around the world, and a growing body of evidence links this to urbanisation, unbalanced diets and the emergence of the so-called “24-hour society”, in which many do shift work. A recent review by Dietrich Büsselberg of the Weill-Cornell Medical School in Qatar and his team summarises this evidence, in order to help understand exactly how they are linked, and develop ways and policies to reverse the trend. People who work nights are exposed to artificial light, and this significantly affects the expression of “clock genes” that synchronize body functions to the day–night cycle. Research shows that clock genes play important roles in controlling cell division and suppressing tumour growth, as well as in regulating cardiovascular and metabolic function. While researchers are still unsure how disrupted circadian rhythms might contribute to the development of these diseases, it seems clear that long-term shift work poses major health risks. Büsselberg and his colleagues make a number of recommendations for reducing these risks. They suggest, for example, that employers consider reducing the number of shift rotations, and increasing the time between shift changes. They also suggest that night shift workers do everything they can to ensure they get good quality sleep— such as avoiding coffee and physical exertion before sleep, wearing eye masks and ear plugs—and that they have regular health checks. “More long-term studies on humans—including groups experiencing regular night shifts—are needed to firmly link different diseases to conditions which disturb the circadian rhythm,” says Büsselberg. “We are planning to have a closer look at how melatonin, the hormone which is released during the night, modulates intracellular calcium concentration, and how this could possibly relate to the induction of cancer. Other Information Published in: QScience.com Highlights, Published by Nature Research for Hamad bin Khalifa University Press (HBKU Press) License: http://creativecommons.org/licenses/by/4.0